Factors that influence foreign direct investment into Nusajaya and its effects towards Malaysia economy / Siti Shukriah Md Sidek - Md Sidek, Siti Shukriah (2010)
This research is to determine the factors that influence the foreign direct investment into Nusajaya and its effects towards Malaysia economy. This research was undertaken with the primary objectives of, firstly is to study the factors as to why, foreign direct investment into Nusajaya and its effects towards Malaysia economy. Secondly is to identify further potential foreign direct investment opportunities in Nusajaya. The paper was studied three major factors such as Economic and Market Factors, and Geographical / Location Factors and Investor Reach which are highly affecting for the inflow of FDI. The research was conducted in two phases. In phase one which involved secondary research such as reviewing of internet, relevant literatures, journals, publications, books and reports. The second phase involved collection of primary data via interview.The respondents were UEM Land employee, Mr. Ong Tee Kiat, Finance Manager and it gain related information and the information would rather be used for this study. In this study, the researcher use the structured interviews where the interviews conducted by the researcher with a predetermined list of question to be asked of the interviews. Interviews are made with people to know the factors influence FDI into Nusajaya and its effects to Malaysia economy. It is easier for the researcher to make the interviews no matter in formal or informal way as well to filter the most accurate reasons as to why FDI flow to Nusajaya and how they could be increased efficiently in the future.